Association Between Antiarrhythmic, Electrophysiological, and Antioxidative Effects of Melatonin in Ischemia/Reperfusion - Sedova, Ksenia A; Bernikova, Olesya G; Cuprova, Julia I; Ivanova, Alexandra D; Kutaeva, Galina A; Pliss, Michael G; Lopatina, Ekaterina V; Vaykshnorayte, Marina A; Diez, Emiliano R; Azarov, Jan E (International journal of molecular sciences, 2019)
Melatonin is assumed to confer cardioprotective action via antioxidative properties. We evaluated the association between ventricular tachycardia and/or ventricular fibrillation (VT/VF) incidence, oxidative stress, and myocardial electrophysiological parameters in experimental ischemia/reperfusion under melatonin treatment. Melatonin was given to 28 rats (10 mg/kg/day, orally, for 7 days) and 13 animals received placebo. In the anesthetized animals, coronary occlusion was induced for 5 min followed by reperfusion with recording of unipolar electrograms from ventricular epicardium with a 64-lead array. Effects of melatonin on transmembrane potentials were studied in ventricular preparations of 7 rats in normal and "ischemic" conditions. Melatonin treatment was associated with lower VT/VF incidence at reperfusion, shorter baseline activation times (ATs), and activation-repolarization intervals and more complete recovery of repolarization times (RTs) at reperfusion (less baseline-reperfusion difference, ΔRT) (p < 0.05). Superoxide dismutase (SOD) activity was higher in the treated animals and associated with ΔRT (p = 0.001), whereas VT/VF incidence was associated with baseline ATs (p = 0.020). In vitro, melatonin led to a more complete restoration of action potential durations and resting membrane potentials at reoxygenation (p < 0.05). Thus, the antioxidative properties of melatonin were associated with its influence on repolarization duration, whereas the melatonin-related antiarrhythmic effect was associated with its oxidative stress-independent action on ventricular activation.
Keywords: depolarization; oxidative stress; Electrocardiography; Electrophysiological Phenomena; melatonin; ischemia; elektrokardiografie; reperfuzní poškození myokardu; krysa rodu Rattus; Cardiac Electrophysiology; Antioxidants; zvířata; Myocardial Reperfusion Injury; reperfusion; elektrofyziologické jevy; srdeční elektrofyziologie; potkani Wistar; fibrilace komor; antioxidancia; Rats, Wistar; Male; srdeční arytmie; antiarytmika; Reperfusion Injury; Ventricular Fibrillation; Anti-Arrhythmia Agents; Heart Ventricles; Rats; Arrhythmias, Cardiac; Animals; mužské pohlaví; arrhythmia; repolarization; srdeční komory; reperfuzní poškození; Melatonin